2016
DOI: 10.1002/mus.25007
|View full text |Cite
|
Sign up to set email alerts
|

Forelimb muscle plasticity following unilateral cervical spinal cord injury

Abstract: Introduction Motor dysfunction and muscle atrophy are well-documented in the lower extremity following spinal cord injury. However the extent and time course of myoplastic changes in forelimb musculature is not clear. Methods Forelimb muscle morphology and fiber type were evaluated following high cervical hemi-lesion injury in rats. Results There was significant atrophy of the ipsilateral extensor carpi radialis longus (ECRL) muscle 2 weeks post-injury, which was subsequently reversed at 8 weeks post-injur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The ability of the AGATHA method to detect changes in gait following a unilateral high cervical SCI was examined using a spinal cord hemisection model 15,38 . Adult male Sprague-Dawley rats (N=9) were obtained from Harlan Scientific and housed at the McKnight Brain Institute Animal Care Facility at the University of Florida.…”
Section: Methodsmentioning
confidence: 99%
“…The ability of the AGATHA method to detect changes in gait following a unilateral high cervical SCI was examined using a spinal cord hemisection model 15,38 . Adult male Sprague-Dawley rats (N=9) were obtained from Harlan Scientific and housed at the McKnight Brain Institute Animal Care Facility at the University of Florida.…”
Section: Methodsmentioning
confidence: 99%
“…In injured lampreys, spinal neurons below the lesion exhibited increased resting membrane potential as well as increased input resistance that, combined with synaptic efficacy enhancement, strongly improved neuronal excitability ( Cooke and Parker, 2009 ). In adult rats with cervical cord hemisection, Gonzalez-Rothi and colleagues reported the transient development of muscular atrophy in the corresponding forelimb ( Gonzalez-Rothi et al, 2016 ), which could have suggested a deficit in motor command due to dramatic and maladaptive rearrangement of spinal motor and/or premotor neurons. But, using pseudorabies viruses during the same period of time in order to track putative added/subtracted connections, the authors did not observe any obvious changes in first-order premotor IN-MN circuitry of the cervical cord ( Gonzalez-Rothi et al, 2015 ), suggesting that no dramatic premotor network reorganization occurred that could explain muscle atrophy-related reduced motoneuronal activity, nor its recovery with time.…”
Section: Compensation After a Unilateral Lesion In Central Motor Circ...mentioning
confidence: 99%